Tożsamościowe wyzwania kobiet sprawujących opiekę nad dzieckiem w związkach jednopłciowych w świetle koncepcji Vivienne Cass - Jowita Wycisk, Jowita Wycisk (Człowiek i Społeczeństwo, 2018)
Development of the contemporary post-industrial society entails the increasing diversity of family life models. People, making individual choices in this field, face new challenges related to identity formation. In the text presented this issue is discussed on the example of women bringing up children in same-sex relationships. The article presents basic information on the same-sex parenting, underlines the importance of the idea of identity integration in psychology and stresses the lack of contiguity between theories of parental identity development and these ones of homosexual and bisexual identity development. An extensive discussion of the Vivienne Cass’s theory of sexual orientation identity development is the basis for the approximation of potential discrepancies in the identity system of non-heterosexual women taking parental roles. Two main factors relevant to the processes of identity formation were distinguished: the order of the development of the sexual orientation identity and parental identity (the planned and reconstructed families differ in this regard) and the way of establishing and maintaining the relationship with the child (other challenges are faced by biological and social mothers). In the summary, questions requiring future empirical exploration were notified.